Africa Communicating: Digital Technologies, Representation, and Power - Alzouma, Gado; Chibita, Monica; Tettey, Wisdom; Thompson, Allan (Institute of African Studies Carleton University, 2013)
What follows is an edited transcript of a panel that took place during the 2013 conference of the Canadian Association of African Studies (CAAS), held at Carleton University. This panel, chaired by Professor Allan Thompson, of Carleton, was called: “Africa Communicating: Digital Technologies, Representation, and Power.”